2015
DOI: 10.1007/s10711-015-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

A topological classification of convex bodies

Abstract: Abstract. The shape of homogeneous, generic, smooth convex bodies as described by the Euclidean distance with nondegenerate critical points, measured from the center of mass represents a rather restricted class M C of Morse-Smale functions on S 2 . Here we show that even M C exhibits the complexity known for general Morse-Smale functions on S 2 by exhausting all combinatorial possibilities: every 2-colored quadrangulation of the sphere is isomorphic to a suitably represented Morse-Smale complex associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Várkonyi and Domokos [26], settling a conjecture due to Arnold (1995), constructed a smooth convex body (called gömböc) with a unique stable and a unique unstable equilibrium. Their discovery has lead to a systematic study of the topological properties of stable and unstable points [13]. However, it is not obvious how to approximate a smooth convex body by a polyhedron with the same stability: Domokos et al [14] show that uniformly random discretization may introduce additional stable equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…Várkonyi and Domokos [26], settling a conjecture due to Arnold (1995), constructed a smooth convex body (called gömböc) with a unique stable and a unique unstable equilibrium. Their discovery has lead to a systematic study of the topological properties of stable and unstable points [13]. However, it is not obvious how to approximate a smooth convex body by a polyhedron with the same stability: Domokos et al [14] show that uniformly random discretization may introduce additional stable equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedra may be regarded as purely geometric objects, however, they are also often intuitively identified with solids. Among the most obvious sources of such intuition are dice which appear in various polyhedral shapes: while classical, cubic dice have 6 faces, a large diversity of other dice exist as well: dice with 2, 3,4,6,8,10,12,16,20,24,30 and 100 faces appear in various games [36]. The key idea behind throwing dice is that each of the aforementioned faces is associated with a stable mechanical equilibrium point where dice may be at rest on a horizontal plane.…”
Section: Introduction 1basic Concepts and The Main Resultsmentioning
confidence: 99%
“…In the literature, the family of convex polyhedra having the same face lattice is called a combinatorial class; here we call it a secondary combinatorial class, and discuss it in Section 5. In an entirely analogous manner, one can define also secondary equilibrium classes of convex bodies, for more details the interested reader is referred to [16]. While it is immediately clear that for any polyhedron P we have f ≥ S, v ≥ U, (1.4) inverse type relationships (e.g.…”
Section: )mentioning
confidence: 99%
“…In the proof of Theorem 2 we have shown that for any discrete 2dimensional point group G and any ε > 0, there is an element K ∈ F whose symmetry group is G and which satisfies d H (K, B 3 ) < ε. Nevertheless, Lemma 4 of [7], and the observation that the smoothing subroutine described in its proof preserves the symmetry group of the body, yield that the statement in (ii) of Theorem 2 for F = (1, 1) c holds under the additional requirement that the body K has a C ∞ -class differentiable boundary.…”
Section: Additional Remarksmentioning
confidence: 99%